Making it on the breadline - improving food security on the Anangu Pitjantjatjara Yankunytjatjara Lands, Central Australia - Amanda J. Lee; Stephan Rainow; Liza Balmer; Rhiannon Hutchinson; Suzanne Bryce; Meron Lewis; Lisa-Maree Herron; Paul Torzillo; Robert Stevens; Margaret Kavanagh; Lisa Wells; Ingrid Kenny; et al. (BMC, 2024)
Abstract Background This longitudinal case study describes the efforts and impacts of community-controlled service organisations on the Anangu Pitjantjatjara Yankunytjatjara (APY) Lands in Central Australia to tackle food security since the 1980s, with a focus on the last decade, particularly during a year of concerted action from mid-2018. Methods The co-designed study comprised an interrupted time series with controls. Availability, affordability, accessibility and sales of foods in the community retail stores on the APY Lands were monitored regularly from 2014 to mid-2022, including by local research teams. Store nutrition policy was updated early 2018. For a year from mid-2018, of the eight communities with stores: (i) two were the focus for concerted intervention, including support from a locally based project officer to help implement the policy and action 105 community requests for nutrition activities (ii) three received usual support to implement the policy; and (iii) three were subject to 'business as usual'. From mid-2019, all communities/stores received usual service, from 2020 with some restrictions related to the COVID-19 pandemic. Results were compared over time, across different community/store groups and with controls. Results In the 12 months from mid-2018, all food security metrics improved most in the two focus communities. Impacts were less marked in the communities without additional support to implement the revised nutrition policy, and even less apparent, although more varied, in the other three communities/stores. Dietary intake improved only in the two focus communities. In all communities from early 2020 most gains eroded due to impacts of the COVID-19 pandemic and other external stressors. Food security metrics, including price of healthy food, appeared more resilient in the focus communities, although diet quality worsened. At all times assessed, healthy diets were unaffordable for welfare-dependant households. Conclusions This co-designed study demonstrates the effectiveness of community-led approaches, confirming that it is possible to improve food security and diet in remote Aboriginal communities. However, sustained action and monitoring, dedicated resources and employment of local people are critical for success. Results also highlight that low incomes are a major barrier to food security.